Perilaku Pemilih dalam Menentukan Keputusan Politik di Indonesia pada Awal Era Reformasi - Maskur, Ali (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
This study aims to analyze voters' behavior in the presidential election in Indonesia. To achieve this goal, researchers limited the period only to the reform period. This is because at this time the political freedom of the people in choosing the president was very protected compared to the previous era. Voter behavior is identified from the political decisions of voters in determining the president and vice president. There are 3 main approaches used to analyze voter behavior, namely sociological, psychological, and rational choices. This research was conducted by using qualitative descriptive method with data collection techniques through observation and documentation. Because researchers are also voters, researchers are the main instrument of this research. The results showed that sociological and psychological factors greatly influenced voter behavior in determining political choices. Emotional voters towards leaders and parties form their attachment to candidates and political parties who ultimately determine their political decisions. In addition, similarities in ethnicity, religion, and regionalism also provide emotional voters in determining their political decisions.